OP06 Evaluating Public Health Interventions: A Neglected Area In HTA. (2019) - Lenoir-Wijnkoop, Irene; Stojanovic, Jovana; Rodrigo, Eva Reviriego; Burton, Alexia Campbell; Hampson, Grace; Gutiérrez-Ibarluzea, Iñaki
Abstract : Introduction: Public health (PH) interventions are crucial for ensuring sustainable healthcare infrastructures. Nevertheless, they represent a neglected area in HTA due to various methodological issues and their complex design that goes beyond clinical setting. Our study provides an environmental scan of HTA initiatives related to the assessment of PH technologies on a global level. Methods: The Initiative for Public Health Outcomes Research and Measurement (INPHORM) interest group has conducted a survey among European and international societies, health bodies and networks during September 2018. The questionnaire evaluates what kind of PH technologies and/or interventions have been evaluated in the last five years, or are planned for the future. Results: Our preliminary findings from November 2018 indicate a total of 94 initiated and 44 completed surveys. Among the completed ones, the majority of respondents came from European countries (36%), followed by North (30%) and South America (16%) countries. Sixty-eight percent of institutions reported engagement in any aspect of HTA in the area of PH (N = 30). Medical aspects of the PH technology are considered by 83 percent of the institutions, followed by organizational impact (67%), economic evaluation (60%) and societal consequences (60%). An average of four PH technologies has been evaluated by the responding institutions in the last five years. In reference to methodological aspects, 90 percent of institutions used a classical HTA approach for evaluating PH interventions, while 40 percent used budget impact analyses. Among the barriers for reaching a decision, conflicting stakeholder priorities, lack of data and clear methodological frameworks were most commonly cited. Conclusions: Data analysis is currently on-going and final results will be presented during the Cologne meeting. This study will allow to raise awareness about the importance of PH interventions in HTA, identify existing gaps and propose future methodological developments.